High gain broadband photoconductor based on amorphous Ga2O3 and suppression of persistent photoconductivity. Issue 42 (10th October 2019) - Zhou, Haitao; Cong, Lujia; Ma, Jiangang; Li, Bingsheng; Chen, Mingzhu; Xu, Haiyang; Liu, Yichun
Abstract : In this work, a high gain broadband photoconductor based on a wide bandgap amorphous gallium oxide film was reported. Meanwhile, a novel short-time heating method was demonstrated to effectively suppress the PPC effect. Abstract : In this work, a new type of photoconductor with high responsivity and gain over a wide spectral range of DUV to NIR using a wide band gap amorphous gallium oxide (a-Ga2 O3 ) thin film was reported for the first time. The responsivity (gain) at deep UV-250, UV-350, VIS-525 and NIR-850 nm is as high as 1099 (5438), 265 (936), 205 (483) and 122 A W −1 (178), respectively. More interestingly, we demonstrate that a novel "thermal relaxation" (TR) process (short-time heating) can effectively reduce the dark current and improve the response recovery time from hours to seconds without reducing the gain of the a-Ga2 O3 detector. The mechanism related to oxygen vacancies and thermal energy and tail state excitation is proposed to explain our experimental phenomena. This result suggests that amorphous Ga2 O3 films have potential applications in high-performance broadband photodetecting devices.